Information technology assists in the innovative development of throwing embroidered balls - Shijun Xu; Yu Wei; Qingbin Sun; Cong Zeng; Ling Li; Fanhui Xu (Scientific Reports)
Abstract This study aims to understand the historical and development of throwing embroidered balls, combine information processing and drone technology to innovate throwing techniques, improve the competitive level and competition rules, promote the high-pole throwing embroidered balls to the international sports. Utilizing literature review method to clarify the evolution history of throwing embroidered balls; using mathematical statistics to analyze the results of competition during the 12th and 13th Guangxi Student Games; Using mechanics analysis and animation production methods innovate throwing techniques. The imperfect competition rules, inconsistent specifications of embroidered balls, and outdated throwing techniques have hindered the healthy development of throwing embroidery ball. The optimal throwing angle range for innovative throwing techniques is between 64° < α < 72°, with the range of throwing speed being between 13.04 m/s < v < 13.70 m/s. When α < 66°, v≈13.70m/s, the ball passes through the lower edge of the top of the circle; When α > 64°, v≈13.04m/s, when α < 72°, v≈13.17m/s, the ball passes through the upper edge of the bottom of the circle. Drone aerial photography technology can assist judges; using animation production techniques to form throwing motion models to guide training can improve competitive skills. Improving competition rules, unifying the use of competition balls, and strengthening the integration of information technology with ethnic sports can effectively enhance the development level of the sport of throwing embroidered balls.